Imaging - (:unkn) unknown (Springer Nature, 2021)
Conventional digital subtraction angiography (DSA) used to be the “gold standard” for the diagnosis of TAK. However, MR angiography has become the most preferred imaging tool for the diagnosis of TAK and is suggested to be the first-choice of modality in recent EULAR guidelines for imaging in LVV. CT angiography is also helpful as a cheap and fast tool to determine the damage associated with vascular stenosis and occlusion. FDG-PET-CT, detecting the vascular distribution of 18-F-FDG, assesses the metabolic, usually inflammatory activity in aorta and its major branches and demonstrate early vascular changes before occlusions or aneursym development during the clinical course of TAK patients. Finally, Doppler US with contrast enhancement is helpful for carotid lesions. The role of imaging to evaluate disease activity is currently an area of promising research, especially for therapeutic clinical trials. © 2021, Springer Nature Switzerland AG.
Keywords: CDUS; CT angiography; Digital subtraction angiography; FDG-PET-CT; MR angiography